Performance of microcredit towards empowerment of women – a case study of saving and credit cooperatives in bardiya district of Nepal - B.K., Laxmi Kumar (Brac University, 2019)
This dissertation is submitted in partial fulfillment of the requirements for the degree of MA in Governance and Development, 2018.